Intestinal Intussusception: Etiology, Diagnosis, and Treatment - Marsicovetere, Priscilla; Ivatury, S. Joga; White, Brent; Holubar, Stefan D. (Clinics in Colon and Rectal Surgery, 2017)
Intussusception is defined as the invagination of one segment of the bowel into an immediately adjacent segment of the bowel. Idiopathic ileocolic intussusception is the most common form in children and is typically managed with nonoperative reduction via pneumatic and/or hydrostatic enemas. In the adult population, intussusception is uncommon and occurs more often in the small intestine than in the colon. It is associated with lead point pathology in most symptomatic cases presenting as bowel obstruction. When lead point pathology is present in adult small bowel intussusception, it is usually benign, though when malignant it is most frequently due to diffuse metastatic disease, for example, melanoma. In contrast, adult ileocolic and colonic intussusception lead point pathology is most frequently primary adenocarcinoma when malignant. The diagnosis is typically made intraoperatively or by cross-sectional imaging. With increasingly frequent CT/MRI of the adult abdomen in the current era, transient and/or asymptomatic intussusceptions are increasingly found and may often be appropriately observed without intervention. When intervention in the adult population is warranted, usually oncologic bowel resection is performed due to the association with lead point pathology.
Keywords: intussusception; intussusceptum; intussuscipiens; bowel obstruction